Languages and compilers for parallel computing 23rd International Workshop, LCPC 2010, Houston, TX, USA, October 7-9, 2010. Revised Selected Papers - Cooper, Keith; Mellor-Crummey, John; Sarkar, Vivek (Lecture Notes in Computer Science, 2011)
This book constitutes the thoroughly refereed post-proceedings of the 23rd International Workshop on Languages and Compilers for Parallel Computing, LCPC 2010, held in Houston, TX, USA, in October 2010. The 18 revised full papers presented were carefully reviewed and selected from 47 submissions. The scope of the workshop spans foundational results and practical experience, and targets all classes of parallel platforms in- cluding concurrent, multithreaded, multicore, accelerated, multiprocessor, and cluster systems.